Die Entwicklung der Trigonometrie in der alten Wilnaer Universität - Chmielewski, B. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Хмелевский. Развитие тригонометрии в старом Вильнюсском университетеB. Chmielevskis. Trigonometrijos išsivystymas senajame Vilniaus universitete